Insecure property rights and growth : the roles of appropriation costs, wealth effects, and heterogeneity - Ngo van Long; Gerhard Sorger (Center for Economic Studies and ifo Institute (CESifo), 2004)
We extend the model of insecure property rights by Tornell and Velasco (1992) and Tornell and Lane (1999) by adding three features: (i) extracting the common property asset involves a private appropriation cost, (ii) agents derive utility from wealth as well as from consumption, and (iii) agents can be heterogeneous. We show that both an increase in the appropriation cost and, when appropriation costs vary across agents, an increase in the degree of heterogeneity of these costs reduce the growth rate of the public capital stock. We also show that, in the interior equilibrium, the private asset can have either a lower or a higher money rate of return than the common property asset.
Keywords: O40; C73; 330; corruption; property rights; growth; appropriation cost; Eigentumsrecht; Wirtschaftswachstum; Korruption; Theorie